1975
DOI: 10.3327/jnst.12.703
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Time Dependent Energy Spectra of Neutrons in a Small Graphite Assembly

Abstract: The time-dependent energy spectra of neutrons have been measured in a small 30 x 3 0 x 30 cm3 graphite assembly by means of the linac-chopper method, with a view to establishing experimental evidence that there is no asymptotic spectrum in such a small assembly, and in order to study the non-asymptotic behavior of neutrons.The arrangement of a polyethylene pre-moderator adjacent to the assembly made the measurements possible with the improvement obtained thereby of the neutron counting statistics. It was indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The data-acquisition system has already been described elsewhere ( 9 ) and the following description will be limited to a summary recapitulation. The time interval between fastneutron burst and mid-point of chopper opening, which determines the delay time, is controlled by phasing the linac and chopper.…”
Section: H Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…The data-acquisition system has already been described elsewhere ( 9 ) and the following description will be limited to a summary recapitulation. The time interval between fastneutron burst and mid-point of chopper opening, which determines the delay time, is controlled by phasing the linac and chopper.…”
Section: H Experimentalmentioning
confidence: 99%
“…INTRODUCTION using this combination of pulsed neutron source and chopper< 2 )- ( 9 ). Study of the changes in time shown by pulsed fast neutrons in various media is useful for investigations on the process of neutron thermalization in moderating material.…”
mentioning
confidence: 99%